Cancer Incidence and Mortality in the Oldest Old: A Nationwide Study in Finland - Tanskanen, Tomas (Am J Epidemiol, 2020)
The world’s population is aging rapidly. This study reports the burden of cancer in the “oldest old” (aged ≥85 years) in Finland, 1953–2017, and estimates age-specific cancer rates in the older population (65–99 years) for 1988–2017. The Finnish Cancer Registry provided data on all cancer diagnoses, cancer deaths, and other deaths in cancer patients in Finland for 1953–2017. Between 1953–1957 and 2013–2017, the proportion of incident cancers in those aged ≥85 years increased from 1.5% to 9.6% (597 to 15,360 new cases), and in 2013–2017, more new cancers were diagnosed at ages ≥85 years than ages <50 years. Cancer incidence and excess mortality attributable to cancer peaked at ages 85–94 years and declined subsequently, whereas cancer-specific mortality continued to increase or plateaued. Due to demographic changes, the number of new cancers in the oldest old has increased substantially in Finland, and currently nearly 1 in 10 cancers are diagnosed in this age group. The increasing cancer burden in the oldest old poses a major challenge for health care and needs to be addressed in designing clinical research and reporting of cancer registries. In older populations with competing risks of death, we propose excess cancer mortality as a measure of cancer-related mortality.